Math, asked by bhattanjali4420, 1 year ago

Two years ago, a man was five times as old as his son. Two years later his age will be 8 more than three times the age of the son. Find the present ages of man and his son.

Answers

Answered by Anonymous
15

Given :

  • Two years ago, a man was five times as old as his son.
  • Two years later his age will be 8 more than three times the age of the son.

To Find :

  • The present age of man
  • The present age of son

Solution :

Let the present age of man be x years.

Let the present age of son be y years.

Case 1 :

Two years ago man's age was five times older as age of his son.

Age of man 2 years ago, (x-2) years.

Age of son 2 years ago, (y-2) years.

Equation :

\longrightarrow \sf{(x-2) =5(y-2) }

\longrightarrow \sf{x-2=5y-10}

\longrightarrow \sf{x-5y=-10+2}

\longrightarrow \sf{x-5y=-8}

\sf{x=-8+5y\:\:\:(1)}

Case 2 :

After 2 years, man's age will be 8 more than 3 times the son's age.

Age of man, 2 years later, (x+2) years.

Age of son, 2 years later (y+2) years.

Equation :

\longrightarrow \sf{x+2=3(y+2)+8}

\longrightarrow \sf{x+2=3y+6+8}

\longrightarrow \sf{x+2=3y+14}

\longrightarrow \sf{x-3y=14-2}

\longrightarrow \sf{-8+5y-3y=12}

\longrightarrow \sf{5y-3y=12+8}

\longrightarrow \sf{2y=20}

\longrightarrow \sf{y=\cancel\dfrac{20}{2}}

\longrightarrow \sf{y=10}

Substittute, y = 10 in equation (1),

\longrightarrow \sf{x=-8+5y}

\longrightarrow \sf{x=-8+5(10)}

\longrightarrow \sf{x=-8+50}

\longrightarrow \sf{x=42}

\large{\boxed{\sf{\red{Present\:age\:of\:man\:=\:x\:=\:42\:years}}}}

\large{\boxed{\sf{\purple{Present\:age\:of\:son\:=\:y\:=\:10\:years}}}}

Answered by Anonymous
4

Answer:

Son's age = 10 Years

Man's age = 42 Years

Step-by-step explanation:

Given:

  • Two years ago , man was five times as old as his son.
  • Two years later his age will be 8 more than three times the age of his son.

To Find:

  • Present ages of man and his son.

Solution: Let the present age of father be x years and present age of son be y years.

Two years ago their ages was

  • Man's age = (x 2) Years
  • Son's age = (y 2) Years

A/q

\small\implies{\sf } x 2 = 5(y 2)

\small\implies{\sf } x 2 = 5y 10

\small\implies{\sf } x = 5y 10 + 2

\small\implies{\sf } x = 5y 8.......(1)

Two years hence their ages will be

  • Man's age = (x + 2) Years
  • Son's age = (y + 2) Years

A/q

\small\implies{\tt } x + 2 = 8 + 3 (y + 2)

\small\implies{\sf } x + 2 = 8 + 3y + 6

\small\implies{\sf } 5y 8 + 2 = 3y + 14 [ From equation 1 since, x = 5y 8 ]

\small\implies{\sf } 5y 6 = 3y + 14

\small\implies{\sf } 5y 3y = 14 + 6

\small\implies{\sf } 2y = 20

\small\implies{\sf } y = 20/2

\small\implies{\sf } y = 10

Hence, Present age of son is x = 10 Years and present age of man is x = 5y 8

x = 5(10) 8

x = 50 8

x = 42 Years.

Similar questions